Die bestuurstaak van die hoof van 'n onderwysersentrum - Bosman, Johannes Nicolaas Fourie (Potchefstroom University for Christian Higher Education, 1984)
The performance of the teacher is one of the most critical factors among the variables within the responsibilities of the schools. It is a truism to state that the potential for teachers to influence pupil learning is very high. Teachers, therefore, bearing in mind such factors as the relative influence of parents, siblings, friends, neighbours, the media etc. are in the best position to optimise the pupils' capabilities for learning. Improving teaching, taking into consideration the very substantial clichés on technology, the knowledge explosion, the problem of ascertaining the tangibility of teaching within a specified period and the variances in teacher and pupil characteristics is a difficult, very complicated and demanding task. The overall importance of the teacher's performance constitutes, therefore, a strong reason to meet the challenge of the changing times. It is difficult to provide good teacher training -to build on this basis is not a simple task. In-service training in an already complex situation has become so important that it brings additional facets to programmes of staff development. Specialised subject approaches which demand specialised training, demand that teachers ought to relate even better to their own content areas and specialised departments. As a consequence, broadly speaking, generic training for teachers fails to provide help with their specialised concerns, especially as regards methodology. Official in-service training programmes often do not solve the more intimate problems of teachers, viz. discipline, internal content problems, effective presentation means of imparting knowledge, current up-to-date information, curriculum development, new approaches and developments in classroom practice, substantive immediate problems and needs that want clarification etc. What generally goes along with these more personal and intimate concerns is the fact that the teacher is looking for reassurances and affirmation that his teaching is effective and perhaps meritworthy in his own eyes. In-service training has become an established facet in all walks of life. The importance, however, is not so much in-service training but renewal. In this respect it is not so much the concept of overhauling knowledge. but rather harnessing and directing teachers' abilities through shared experiences and information, by providing new information, assessing it by fresh or new viewpoints and to stimulate each other to look at different approaches to old or freshly experienced problems. These facets can be reduced to on-going or continuing or adult or informal or non-formal education. A dualway communication between members of the teaching profession is necessary to fulfil the needs of renewal or continuing education. This fulfilment has been embodied in the concert in what is nowadays called 'teachers' centres'. The possessive form denotes that it belongs to teachers -from teachers for teachers by teachers. An informal training ground is established to strengthen the ability of teachers to help them meet their professional, personal and school objectives. It provides the additional support and assurances which the traditional formal in-service courses cannot normally supply. The uniqueness and force of teachers' centres lie therein that the practicing teachers themselves identify problem areas and co-ordinate with the centres to arrange whatever is necessary to bridge these problems. The basic philosophy underlying a teachers' centre is to remove boundaries between all educational institutions and those who practise teaching. These boundaries tend to lead to inflexibility and unnatural attitudes in a field where understanding, mutual acceptance of differences in leaching approaches and awareness of the contribution each can make to better teaching practices, are desirable. There are no reliable definitions of teachers' centres. The possessive form 'teachers' centres' implies that it implicates, from the roots upwards, everyone who is directly concerned with teaching. This in turn implies that whatever is presented at a teachers' centre has been identified either as a need, a problem area or as a renewal in the educational field as well as desire to improve on existing abilities or provide for a lack or shortcoming in knowledge, methodology, etc. by the practicing teachers themselves. This act of 'renewal' takes place informally, in an atmosphere where the abstract fear of officialdom is negated by a sense of acceptance together with a spirit of communicativeness, charitability, professional conviction and in a supportive learning environment. As in any organisation there has to be a structured system to meet and execute its requirements and objectives. Although most teachers are not neophytes and they realise through experience and recognise that they have considerable knowledge and expertise about their work, clear purposes for the operation of the teachers' centre should be set and parameters established to meet and conform to local and departmental goals and objectives. In fact, there has to be a structured approach to allow teachers' centres to become a life-giving source to teachers. The benefits to the teachers for their investment of, time, ideas, energy, sharing of expertise in a wide and varying field depend upon the strength of the centre. There has to be programmed planning. Teachers' centres can only justify their existence through the services they render. Activities or programmes are planned around teachers' expressed interests and perceptions of their own and others' staff developmental needs. Teachers work collaboratively on a common need or interest they have identified or have been led to identify. This collaboration is very important for the development of new attitudes to own resourcefulness and expertise. If teachers are given enough time and support they are in the best position to realise and to accept their own needs and seek help in solving them. In essence the teachers' centre is a support system for teachers who lean on the elements of the system Which traditional in-service training generally does not offer. Teachers' centres can effectively respond to teachers' individualised needs which are not easily accommodated in university, college or in-service based programmes. But, quality programmes do not just happen, but are the result of a many-faceted and deliberate process of programme development. The programme should be a learning exchange and the needs that are established should be largely community needs and grow out of the local talent as far as possible. Discovering needs and establishing them are as essential for planning a dynamic programme as finding someone who can verbalise and concretise the need and present it in such a manner that the teachers can relate to each other. To establish a need is also to establish a talent for fulfilling it. Various ways of discerning and establishing needs are available, viz. formal means, e. g. correspondence, or informal means, e. g. personal contact arranged in a relaxed atmosphere. Through personal contact the teachers can be guided to articulate their needs. Once a contact has been firmly established, maintained and followed up, it leads to the achievement of personal and professional goals, for career advancement and improved performance in classroom practice. All in all, the teachers' centre is more than the normal organisation; it is a network of professionally qualified teachers and others devoted to the educational task, either by discerning needs or by giving their talents. The manner in which it is done conveys the true identity of the centre. Contrary to the popular belief, the centre is not necessarily a place, but people. Wherever a programme on educational matters is administered and co-ordinated by the teachers' centre on the conditions outlined above, as such the teachers' centre concept is functioning, no matter whether it is in the building which houses the offices of the entire head, staff and resources or in a small rural school building. The teachers' centre per se is a concept and attributable to the philosophy underlying all teachers' centres. Although teachers' centres are unique in their own right as to their structure, performance and execution, they are recognised by the philosophy they reflect: * to fulfil the immediate and actual professional needs of practicing teachers by any means which are viable; * to provide and encourage interaction between teachers from all walks of the educational field. i.e. from beginner-teachers to educationalists in academic positions and others holding executive statuses In the organisatlon of education departments: * to strengthen the liaison between the various educational institutions, i.e. from pre-primary to tertiary educational institutions; * to delve into and to exploit the enormous expectancy and experience represented by the teaching corps; * to create a neutral arena where teachers feel free from officialdom, where a spirit of acceptance and sharing exists, where goodwill and professional conviction are prevalent, and where ideas, advice and ideals are shared in the establishment of sound classroom practices in various subject disciplines. The concept of the teachers' centre is still relatively new. The danger which exists is that teachers may consider the centre as a panacea for all their problems which is not the case. Without stifling anything that comes in. the need for filtering requests is a very pertinent one. Whenever people are concerned with their profession and are earnest in their task delineation, there is no such thing as an unimportant question or a superficial request. Every question or request sent in must be researched carefully. Surface statements of requests may conceal very substantive problems because they were initially ineptly phrased or formulated. Rephrasing a request or letting a neutral subject workgroup consider it may cast new light on it or reveal new dimensions. Assessing the needs of practicing teachers is a major priority, but on the same level, presenting programmes to accommodate these needs, is another major function of the centre. The integration of theory and practice strengthens the teachers' ability. Teaching competence in general or specialised areas of interest are improved when co-operating teachers, colleagues from colleges of education and university lecturers have the opportunity to share their knowledge and skills in these areas. This co-operation may lead to such matters as pre-service requirements, informal, non-formal, continuing education, curriculum development, evaluation procedures and the refinement of educational matters in general. Working together to derive workable solutions to both theory and practice, the constant exchange and debate of theories, ideas, strategies, implementation of various educational resources, etc., may enable both sides of the profession (theorists and practitioners) to understand each other better, provided educational biases are set aside. In the midst of all this is the person responsible for giving substance to an organisation to fulfil all the requirements stated above. Vere de Vault, et al. (1979:166) states that the warden (head of the centre) has a major influence on the nature of the centre as every centre has its own character "... while at the same time maintaining certain thematic consistencies with other centres across the country". It was found during the research that many sources support the opinion that the head of a centre determines the configuration of his centre. No one has made a clear distinction of what the tasks of such a head entail. In fact, no source has even attempted to formulate a defInition of a centre, or what is required of the person (warden, director, supervisor, administrator, head) who is to organise, administer and conduct such a centre. Some even make it quite clear that no attempt should even be made to try lo de fine a teachers' centre or the person who is to head it. Such attempts would reduce the centre to something which could lose its appeal for teachers. In the investigation to determine and to delineate to a certain extent the various tasks a head of a teachers' centre must perform. one fact has become crystal clear. There are certain 'thematic consistencies' among the various centres across the world and in the RSA. Yet, each centre has a character of its own and has certain individual traits that makes it uniquely different from any other centre. This difference is ascribed to the head of the centre who conducts it in accordance with his own individual managerial style, the demographical insight he has of his region and teachers and his personal dealings with the teacher contact groups he has succeeded in establishing to advise him in his task. A questionnaire was sent out to the teachers' centres in the RSA. A study of their replies has revealed a picture of the manner in which the respective heads of centres manage their centres. Although a clear line can be drawn through the already universally established concepts of good managementship, each centre head also revealed his particular approach and individual style. At the same time, however, it was possible to find similarities which have been taken up in a diagrammatical representation of the head's task. The suggested guidelines are in no manner prescriptive. It gives a global insight into what has been revealed by a study of the relevant literature and the empirical investigation that the management of a teachers' centre is a very complex and intricate operation that entails many factors. Amongst these are the teachers with whom the centre head has to work. Short descriptions of the three major types of teachers are given. viz. the committed, the apathetic and the teacher with a stressful personality. Some of their characteristics are outlined. Descriptions of eight managerial styles are given which should be applicable to a teachers' centre. The four main managerial functions which can be considered to be universal planning, organisation, control, leadership are explained. Each has in essence various built-in characteristics. e.g. communication, motivation, style of leadership, delegation, decision-making, etc. Particular emphasis was placed on the creation of an 'ethos' of an organisation's culture. In no way, however, either in the guidelines revealed or in the diagram presented, has any attempt been made to be prescriptive. This would have been a futile exercise. Suggestions for further research on teachers' centres and for teaching in general have been made in the last chapter. The research has to be followed up for it has already been claimed by a number of sources that the teachers' centres have definitely brought about a change in the professional growth and attitude of teachers towards their work. No empirical evidence exists to support these claims. Most important of all has been the researcher's viewpoint that the head of a centre must hold certain Christian values, not because of the Education Act. No 39 of 1967, but because of the moral implications of human relationships in the organisation. Garnering or generating knowledge is not a final requirement. The qualities, norms, and spiritual welfare take precedence over all other human activities. The Christian teacher must inculcate Christian values in the child or procreate the Christian values already instilled by Christian parents. The head of the centre's educational objective is adjusted to the Scriptural view of the origin, nature and ultimate destination of man.
Proefskrif (DEd)--PU vir CHO, 1984
Keywords: Onderwysers; Indiensopleiding; Universiteits- en kollegehoofde; Taakomskrywings